Dissecting the attitudes of political science students towards democracy and the 2004 elections in Indonesia - Tyson, Adam; Tyson, Paul (Routledge, 2007)
Students’ attitudes towards Indonesia’s transition from an authoritarian era to democracy varied from strong support for the democratic transition to nostalgia for the authoritarian era’s strong leadership and economic prosperity. A sample of 317 students from three Indonesian universities was asked to rate the importance of political, economic, legal and social democratic principles. In addition to concerns about corruption, economic decline and security, students differed significantly centring on the importance of legitimate elections, representation, tolerance, accountability, human rights and gender equality. The majority of students were pessimistic about the elections; paradoxically some students optimistic about the general elections rated democratic principles the least important. After discussing the implications, political attitudes about democracy and elections were related to cognitive consistency and dissonance theory.